Rebalancing the Agenda. (3rd July 2018) - Taylor, Max
ABSTRACT: In welcoming the recognition that victimization through terrorism is a significant factor in our thinking about terrorism, a case is made for greater engagement of Civil Society, through nongovernmental organizations, in the development of policy in this area. It argues for a rebalancing of policy toward the "passive victims" of terrorist activity, and a recognition that the lived experience of harm done by terrorism is not mitigated by either context or alleged justification. A case is also made for using the study of victimization as a focus for interdisciplinary work on terrorism, recognizing that expertise in this area lies both within and outwith government.